2018
DOI: 10.1002/hsr2.53
|View full text |Cite
|
Sign up to set email alerts
|

A pilot longitudinal study of anti‐Müllerian hormone levels throughout gestation in low risk pregnancy

Abstract: Background: Anti-Mϋllerian hormone (AMH) plays an important role regulating ovarian sensitivity to follicle-stimulating hormone and luteinizing hormone in folliculogenesis. Anti-Mϋllerian hormone is well established as a biomarker of ovarian reserve but may also have utility in predicting pregnancy outcomes. Few studies have described AMH levels in pregnancy and, among those that have, most have used cross-sectional study designs and are limited to participants seeking fertility treatment. Our aim was to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…The present study represents the 2 nd largest study available exploring this question by employing a longitudinal design. The kinetics of AMH between the 1 st and 2 nd trimesters of pregnancy have been evaluated by four other longitudinal studies, which also found a decrease in AMH during pregnancy (Freeman et al, 2018, Koninger et al, 2013, Nelson et al, 2010, Pankhurst et al, 2016. The median AMH percentage decrease in these studies varied from 13.5% to 35.9% from the 1 st to the 2 nd trimester, consistent with our finding of a median 39.8% decrease during this period.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The present study represents the 2 nd largest study available exploring this question by employing a longitudinal design. The kinetics of AMH between the 1 st and 2 nd trimesters of pregnancy have been evaluated by four other longitudinal studies, which also found a decrease in AMH during pregnancy (Freeman et al, 2018, Koninger et al, 2013, Nelson et al, 2010, Pankhurst et al, 2016. The median AMH percentage decrease in these studies varied from 13.5% to 35.9% from the 1 st to the 2 nd trimester, consistent with our finding of a median 39.8% decrease during this period.…”
Section: Discussionsupporting
confidence: 88%
“…The median AMH percentage decrease in these studies varied from 13.5% to 35.9% from the 1 st to the 2 nd trimester, consistent with our finding of a median 39.8% decrease during this period. One longitudinal study of 30 women took serial AMH measurements at five time points throughout pregnancy demonstrating decreasing AMH with increasing gestation, with the largest decline in the 1st trimester between 7-and 14-weeks gestation (Freeman et al, 2018). This finding may suggest that the initial steep decline in AMH levels had already begun for women in our cohort whose 1st AMH measurement was taken at 10-13 weeks gestation.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Most studies reported a decline in AMH levels from the late first trimester of pregnancy onwards ( 20 , 41 , 42 ). Others observed a decline earlier in pregnancy, between 7 and 14 weeks of gestation ( 43 ). The analyzed AMH levels in those studies were not adjusted for maternal age, smoking, BMI, education level, maternal ethnicity, parity, or fetal sex.…”
Section: Discussionmentioning
confidence: 99%